Pendidikan Moderasi Beragama: Kontribusi pemikiran Islam dan Kebangsaan Ahmad Syafii Maarif - Darmawan, Rivaldi; Nugroho, Wahyu Budi (Universitas Muhammadiyah Yogyakarta, 2025)
This article dialogues the Philosophy of Islamic and National Thought of Buya Syafi'i Ma'arif which is used as the basis for religious moderation education of Mu'allimin santri. His actual thinking about the discourse of Islam and nationality is no doubt, so that it has a major contribution to the development of religious moderation. One of the productive Muslim scholars with his pithy mindset makes Mu'allimin Muhammadiyah Yogyakarta students emulate Buya Syafii's attitude and construction of thinking in terms of Islam and nationality. Descriptive qualitative is the approach used in this research. The research carried out at Mu'allimin Muhammadiyah Yogyakarta has passed the process of interaction and observation of Mu'allimin students so as to get conclusions, among others: Buya Syafii completed his secondary education at Mu'allimin Muhammadiyah Yogyakarta so that there is an emotional closeness between Buya and Mu'allimin. Not limited to exemplary Islamic and national insights, Mu'allimin students are also directed to emulate the moral majesty of Buya Syafii. Formal learning and informal activities become a medium for Mu'allimin students to emulate the figure of Buya Syafii. On the other hand, Buya Syafii Ma'arif's thoughts in the fields of Islam and nationality which are in line with moderate principles are used by Mu'allimin as the basis for religious moderation education. Religious moderation education is implemented by Mu'allimin practically and theoretically. Practical aspects are implemented through dormitory activities and community service. While the theoretical aspects are obtained by Mu'allimin students during KBM activities in the classroom. Both have interrelated functions so that they have a positive influence on the process of religious moderation education.